Pengaruh Kearifan Lokal Malempu Na Mapaccing dan Peran Aparatur Desa terhadap Kepatuhan Bayar Pajak Bumi dan Bangunan (PBB) pada Suku Bugis di Desa Sibualong - Ryan Farham; Ni Made Suwitri Parwati; Muhammad Ilham Pakawaru; Chalarce Totanan (Journal of Economics and Management Scienties, 2026)
This study aims to analyze the influence of Malempu na Mapaccing local wisdom and the role of village apparatus on community compliance in paying Land and Building Tax (PBB) in Sibualong Village. The objects of this study were Bugis ethnic PBB taxpayers residing in Sibualong Village. This study utilized a quantitative approach with an explanatory research type and a cross-sectional design. Primary data were obtained through the distribution of questionnaires to 136 respondents selected using a purposive sampling technique, while data analysis was performed using multiple linear regression with the aid of SPSS. The results showed that the Malempu na Mapaccing local wisdom had a positive and significant effect on community compliance in paying PBB (β = 0.605; p = 0.001). The role of the village apparatus also had a positive and significant effect on community compliance (β = 0.530; p = 0.001). The coefficient of determination (R²) value of 0.523 indicates that both variables are able to explain 52.3% of the variation in community compliance in paying PBB. This study concludes that Malempu na Mapaccing local wisdom and the role of village apparatus have a positive and significant effect on community compliance in paying Land and Building Tax (PBB) in Sibualong Village.